Thermal and electrostatic tuning of surface phonon-polaritons in LaAlO3/SrTiO3 heterostructures - Zhou, Yixi; Waelchli, Adrien; Boselli, Margherita; Crassee, Iris; Bercher, Adrien; Luo, Weiwei; Duan, Jiahua; van Mechelen, J.L.M.; van der Marel, Dirk; Teyssier, Jérémie; Rischau, Carl Willem; Korosec, Lukas; et al. (Nature communications, 2023)
Phonon polaritons are promising for infrared applications due to a strong light-matter coupling and subwavelength energy confinement they offer. Yet, the spectral narrowness of the phonon bands and difficulty to tune the phonon polariton properties hinder further progress in this field. SrTiO 3 – a prototype perovskite oxide - has recently attracted attention due to two prominent far-infrared phonon polaritons bands, albeit without any tuning reported so far. Here we show, using cryogenic infrared near-field microscopy, that long-propagating surface phonon polaritons are present both in bare SrTiO 3 and in LaAlO 3 /SrTiO 3 heterostructures hosting a two-dimensional electron gas. The presence of the two-dimensional electron gas increases dramatically the thermal variation of the upper limit of the surface phonon polariton band due to temperature dependent polaronic screening of the surface charge carriers. Furthermore, we demonstrate a tunability of the upper surface phonon polariton frequency in LaAlO 3 /SrTiO 3 via electrostatic gating. Our results suggest that oxide interfaces are a new platform bridging unconventional electronics and long-wavelength nanophotonics. Phonon polaritons are promising for infrared applications while it is difficult to tune the phonon polariton properties. Here, authors report a thermal and electrostatic tuning of surface phonon polaritons in heterostructures of LaAlO3/SrTiO3.